Determinantes do alcance das metas do programa de qualificação das ações de vigilância em saúde em municípios da região TOPAMA - Melo, Quézia Catharinne Cavalcante de (Universidade Federal do Tocantins, 2024)
Introduction: The “Projeto de Formação e Melhoria da Qualidade da Rede de Atenção à Saúde” (QualiSUS-Rede) covers health regions, defined based on peculiar conditions. Among these regions is the Interfederative Health Network, TOPAMA, a state border region in the Legal Amazonia, located in the extreme north of the state of Tocantins, bordering the states of Pará and Maranhão. This region presents an unfavorable scenario in terms of meeting the goals of the Health Surveillance Actions Qualification Program (PQA-VS), which comprises the Ministry of Health's initiatives to improve the Unified Health System (SUS) and improve the continuous and progressive process of health surveillance actions. Objective: To identify the determinants listed by the health surveillance teams, which affect the achievement of activities to reach the goals of the PQA-VS, in 30 municipalities in the TOPAMA region. Methods: This dissertation is an excerpt from the “QualiTOPAMA Central Project – Qualification of Health Surveillance Actions, Strengthening and Organization of the Interfederative Health Network (TOPAMA Network)”. It was built around the production of two scientific articles on the subject. Results: Both produced articles demonstrated the need to strengthen Permanent Education in all the studied cities, in addition to the need for greater integration between health surveillance and primary care. In article 1, the municipalities with the worst performances were identified for the fulfillment of the 14 goals of the PQA-VS and in this same study it was possible to observe that no municipality reached all the agreed indicators. In article 2, the profile of the civil servants of the 30 municipalities participating in the research was described, as well as the identification of the main difficulties identified by health professionals in achieving the program's goals, in addition to correlating weaknesses with the difficulty in meeting the indicator. Conclusion: The PQA-VS is a very broad program that contributes to the improvement of the SUS. The goals and indicators provide municipal management with an assessment and identification of its weaknesses and strengths. It is a program that aims the planning and implementation of public health measures for the protection and promotion of the population's health, in addition to the prevention and control of risks, injuries and diseases.